Drug Formulasi paper soap ekstrak etanol dedak padi (Oryza sativa L.) dan uji aktivitas antibakteri terhadap bakteri Escherichia coli dan Staphylococcus aureus - Zannah , Muhamad; Dalimunthe , Gabena Indrayani; Lubis , Minda Sari; Yuniarti, Rafita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Paper soap is soap in the form of thin sheets resembling paper. Rice bran from rice milling waste contains antibacterial compounds. The aim of this research was to formulate paper soap from rice bran ethanol extract and to determine its antibacterial activity. This research is a type of experimental research carried out in a laboratory. Includes steps such as taking and identifying samples, preparing and making ethanol extract of rice bran (Oryza sativa L.), and testing antibacterial activity against Escherichia coli using the Disc Disc method, where the inhibition zone of the ethanol extract of rice bran and the paper soap preparation is containing rice bran extract (Oryza sativa L.) was observed and measured as a result of the antibacterial activity test. The results of this research show that the ethanol extract of rice bran contains chemical compounds, namely alkaloids, flavonoids, saponins, tannins, triterpenoids/steroids and glycosides. Rice bran ethanol extract has characteristics in accordance with the 1989 MMI requirements. The results of determining the antibacterial activity of rice bran ethanol extract produce an inhibition zone against Escherechia coli bacteria ranging from 5mm - 12.5mm and Staphylococcus aureus ranging from 5.5 mm-16.67 mm. The results of the paper soap evaluation test, organoleptic examination, thickness examination, weight uniformity test, stability test, foam power test met the requirements and in the irritation tests F0, F1, F2 and F3 did not irritate the skin, in the hedonic test the most preferred formula was F1. The results of determining the antibacterial activity of paper soap produced an inhibition zone for Escherechia coli bacteria ranging from 8.16mm - 12.5mm and Staphylococcus aureus ranging from 15mm-14.83mm. From the research results it can be concluded that rice bran ethanol extract can be formulated into paper soap and has antibacterial activity.